THE EFFECT OF ORGANIZATIONAL COMMITMENT AND WORK ENVIRONMENT ON JOB SATISFACTION OF EMPLOYEES OF THE SOUTH COAST DISTRICT INSPECTORATE OFFICE - Badri, Juarsa; A, Megaliza. (LPPM Universitas Bina Bangsa, 2022)
This study aimed to analyze and prove the effect of organizational commitment and work environment on job satisfaction of employees in the Inspectorate Office of Pesisir Selatan District. The data analysis technique used to test the hypothesis is multiple linear regression. The sampling technique used is saturated sampling, while the number of samples used for analysis is 47 people. In this study, there are two independent variables: organizational commitment and work environment. Based on the multiple linear regression analysis results, it was found that the variable organizational commitment has a positive and significant effect on job satisfaction, and the work environment has a positive and significant effect on job satisfaction in the Inspectorate Office of Pesisir Selatan District. This study recommends practically to the Inspectorate Office of Pesisir Selatan District to continue to improve employee job satisfaction optimally in achieving organizational goals in the future